Legal Construction of Foundations as Parent Companies to Limited Liability Companies (LLCs) in the Perspective of the Foundation Law and the Limited Liability Company Law - Shafiya, Tiara Alvyya; Naibaho, Cecilya Regnawaty; Nahdi, Nazir Saleh; Gultom, Elisatris (Universitas Islam Negeri Sumatera Utara, 2025)
A foundation, as a legal entity aimed at social, religious, and humanitarian purposes, often faces legal issues when establishing or controlling a Limited Liability Company (LLC) to support its social activities. This study aims to examine the legal relationship between a foundation as the parent company and the LLC as the subsidiary, based on the provisions in the Foundation Law and the Limited Liability Company Law. The research also analyzes the legal consequences arising if one of the entities incurs losses, whether the foundation or the LLC. The results show that although a foundation can establish an LLC, deviations occur in practice, such as the concurrent roles of foundation managers in the LLC, leading to conflicts of interest and misuse of funds. The case of the Aksi Cepat Tanggap (ACT) Foundation illustrates the importance of separating the foundation's social activities from the business interests of the LLC. Therefore, legal reform is needed to strengthen oversight, transparency, and accountability in the relationship between foundations and LLCs.